The Effectiveness of Memory Strategies Training on Students’ Vocabulary Retention: An Action Research at Phuong Dong University - Nguyễn, Thị Huyền Trang (ĐHNN, 2017)
This study was conducted as an action research in which students were taught on how to process vocabulary deeply by applying some vocabula ry learning strategies (VLS). The study first aimed at identifying the vocabulary problems that students are facing with; evaluating the improvement of students’ vocabulary retention with some helpful memory strategies, namely structured reviewing, using mechanical techniques, using imagery and placing new words into a context ; finding out which strategies are the most popularly used among students; and finally collecting students’ attitudes towards the strategy training scheme, four sub - memory strategies and their suggestions for a better future teaching and learning program. For the accomplishments of these purposes, 28 first - year students in one class at Phuong Dong university, Vietnam were involved in the study. The data instruments varied from a Vocabulary Knowledge Scale (VKS) test, a group - interview, learners’ diaries, pre-test/post-tests to a questionnaire. Through the VKS test and the group interview, the results revealed that among many obstacles students encountered in their independent vocabulary learning, lack of remembering techniques was the biggest problem. Learners’ diaries noticeably indicated students’ equal concerns for all four sub-memory strategies, and especially for “using imagery” strategy. The results from the pre - test and the two post- tests helped to prove the effectiveness of using memory strategies in both short - term and long - term vocabulary learning. Finally, students’ positive attitudes towards both the strategy training scheme and four memory strategies and their suggestions about the future learning and teaching vocabulary were comprised in the last instrument - questionnaire. On this basis, the study gave some implications for teachers’ preparation, classroom practices and future research